Production of D6,7-anhidroeritromisin-A from Saccharopolyspora erythraea ATCC 11635 culture - Khairan .; Umar Anggara Jenie; Retno S. Sudibyo (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Erythromycin has been used widely to prevent infection diseases which caused by Staphylococcus. However erythromycin is unstable and decomposed in an acid condition. This unstability erythromycin is conducted by due to a nucleophylic attack of the C6-hydroxyl group of erythromycin to its C9-carbonyl group. This Decomposition can be avoided by modification the erythromycin structure; such as omitting the C6-hydroxyl group. Biomodification for omitting the C6-hydroxyl group can be conducted by inhibition the activity of enoyl reductase in fourth step of the biosynthesis 6- deoxyerythronolid-B. The inhibition process could carried out by an addition of an antimetabolite isonicotonic hidrazide (INH) into the fermentation of erythromycin production. By the enoyl reductase inhibition, the microbe will produce D6,7-Anhydroerythromycin-A which is more stable in an acidcondition than erythromycin-A. This research is to produce derivative D6,7-Anhydroerythromycin-A by addition of INH into a culture of Saccharopolyspora erythraea ATCC 11635 in medium basal and Hutchinson. Selection of medium for fermentation of Sac. erythraea ATCC 11635 for D6,7-Anhydroerythromycin-A production was done out of two media: basal medium with palm oil and Hutchinson medium. The two media were treated with an additional 0,2% INH as an antimetabolite.Hutchinson medium yielded the highest product of D6,7-Anhydroerythromycin-A. The FT-IR spectrometric analyzes of metabolite showed a stretching vibration of C=C conjugated group at wave number 1602,7 cm-1. This C=C conjugated vibration indicated the existence of double bond between C6 and C7 (D6,7), this confirmed that isolate-C contained D6,7-Anhydroerythromycin-A (the possibility of D6,7 was positive).Key words: enoyl reductase, D6,7-anhydroerythromycin-A, isoniazid (INH)